2007
DOI: 10.1002/elps.200600808
|View full text |Cite
|
Sign up to set email alerts
|

Review of aqueous chiral electrokinetic chromatography (EKC) with an emphasis on chiral microemulsion EKC

Abstract: Review of aqueous chiral electrokinetic chromatography (EKC) with an emphasis on chiral microemulsion EKCThe separation of enantiomers using electrokinetic chromatography (EKC) with chiral microemulsions is comprehensively reviewed through December 1, 2006. Aqueous chiral EKC separations based on other pseudostationary phases such as micelles and vesicles or on other chiral selectors such as CDs, crown ethers, glycopeptides, ligand exchange moeities are also reviewed from both mechanistic and applications pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 172 publications
0
45
1
Order By: Relevance
“…In order to delineate the involvement of individual chiral microemulsion components in the overall free energy difference, single-chirality formulations of RXX for the chiral surfactant, XSX for the chiral cosurfactant, and XXR for the chiral oil were previously tested. In the previously completed studies, it was found that XSX [29] and XXR [31] did not give any discernable enantioselectivity, thereby precluding contributions from the cosurfactant or oil. The one-chiralcomponent microemulsion SXX was not analyzed because it has the opposite stereochemistry from RXX and as such should differ only in elution order [40].…”
Section: Enantioselective Synergisms With Three-chiralcomponent Micromentioning
confidence: 95%
See 4 more Smart Citations
“…In order to delineate the involvement of individual chiral microemulsion components in the overall free energy difference, single-chirality formulations of RXX for the chiral surfactant, XSX for the chiral cosurfactant, and XXR for the chiral oil were previously tested. In the previously completed studies, it was found that XSX [29] and XXR [31] did not give any discernable enantioselectivity, thereby precluding contributions from the cosurfactant or oil. The one-chiralcomponent microemulsion SXX was not analyzed because it has the opposite stereochemistry from RXX and as such should differ only in elution order [40].…”
Section: Enantioselective Synergisms With Three-chiralcomponent Micromentioning
confidence: 95%
“…In cases where Eq. (10) does not hold, the reason is postulated to be a synergistic interaction between two or more different chiral components of the microemulsion [29][30][31]. The nature of the synergistic effects, beneficial (higher than expected enantioselectivity) or detrimental (lower than expected enantioselectivity), is defined in Eqs.…”
Section: Enantioselective Synergisms With Three-chiralcomponent Micromentioning
confidence: 97%
See 3 more Smart Citations